Temple rites and temple servants: Religion's role in the survival of Kerala's Kutiyattam drama tradition - Bruce M. Sullivan (Intenational Journal of Hindu Studies 1(1) 1997, 1997)
Classical drama in India is an ancient tradition which has preserved many texts of plays, treatises on literary theory and poetics, and learned commentaries. Even more significantly, classical drama is not merely a found object of literary archaeology, but is still a living tradition today in south India. Kerala's performance tradition called Kutiyattam ('acting together') is unique, as it is the only surviving genre of classical Sanskrit theater with an unbroken lineage (par~.ara) of masters and pupils during the last nine hundred years. I Indeed, its roots may well go back even farther in history) The Kfi.tiyi..rtam tradition of enacting classical Sanskrit dramas is largely in conformity with the guidelines provided in the Natyasasthra of Bharata, the definitive ancient text on dramaturgy. 3 Kfi.tiy~..th.am is a regional variant of the classical tradition, its unique features being due to Kerala's culture and Kfi.tiy~.t.tam's preservation within the sanctuary of the Hindu temple for centuries. One of the major reasons for the tradition's longevity is that Hindu kings, who donated to support Hindu temples as part of their social and religious duties, ruled Kerala without interruption; Muslims never establishedcontrol in Kerala as happened elsewhere to the north. Because of its antiquity, the K~.tiy~am tradition is profoundly significant for our understanding of the dramatic art in ancient India?